Inclusive Development and Community Rights in Pelabuhanratu’s Just Energy Transition - Theofillius Baratova Axellino Kristanto; Lukas Andri Surya Singarimbun; Izzatinnisa Izzatinnisa (Lembaga Penelitian, Universitas Warmadewa, 2025)
Climate change urges countries to adopt environmentally friendly energy production methods. The Co-firing Power Plant in Pelabuhanratu, part of the Just Energy Transition (JETP) partnership, aims to fulfil Indonesia’s commitment to energy transition while addressing local social justice issues. This research examines the complexities of local community rights in Indonesia’s just energy transition, with a focus on the co-firing power plant, particularly in Pelabuhanratu. A neo-Gramscian approach is used to analyse power dynamics and social transformation through concepts of counter-hegemony and coalition-building. The research methodology includes in-depth interviews, participatory observations, focus group discussions, and document analysis to capture various stakeholder perspectives and experiences. The biomass co-firing supply chain at Pelabuhanratu involves key actors such as Panglong, Suppliers, Agents, and CFPP, who are responsible for sourcing and distributing sawdust to the power plant. While the program creates economic opportunities, the main challenges include biomass price fluctuations, price manipulation by intermediaries, and environmental impacts from biomass burning, such as air pollution and deforestation of young trees. Women's participation in the program is limited, with most locals engaged in low-skilled jobs. The research also shows that negative environmental and social impacts remain significant barriers to achieving a just energy transition. The neo-Gramscian approach reveals that, despite material benefits, local communities remain trapped in power relationships that favour the dominant class, with little room to challenge existing policies. A more inclusive and just energy transition requires the formation of alternative institutions, improved education, and better access to resources.